The experience of mothers practising kangaroo mother care in the East London hospital complex - Muteteke, Dorcas K. (Department of Paediatrics and Child Health, 2023)
Mortality and morbidity due to low birth weight and pre-term birth are high, especially in developing countries where resources and qualified neonatal staff are scarce. There is a need to find measures that reduce the cost of care for low birth weight and pre-term babies without sacrificing quality. Conventional methods of care, where infants are exclusively cared for by the nursing staff using incubators, are very costly. In addition~ morbidity and mortality are adversely affected by some conventional low birth weight care procedures and better means of care are needed to avoid these extra risks. It is therefore important to find a substitute for conventional care without putting infants' lives in danger. The Kangaroo Mother Care (KMC) method could be a viable solution, since it addresses many of the problems encountered with the conventional method. KMC is the practice of caring for low birth weight neonates by keeping them in skin-to-skin contact with their mother's chest. The length of time that the infants are placed in this position can vary from a few hours a day, to 24 hours a day. KMC provides warmth and care; it promotes bonding, breastfeeding and early discharge. Published studies of this method also indicate that KMC decreases mortality and costs while improving health outcomes. Much research has been done on the use of KMC with low birth weight children in different settings, but less has been done on its practice from the mother's point of view. This study explores the quality of the mothers' experiences with KMC in the East London Hospital Complex, consisting of the Cecilia Makiwane Hospital (CMH) and the Frere Hospital (FH), where it has been practised since July 1999. The aim of the study was to identify factors that influenced mothers' knowledge, attitudes and opinions regarding the practice of KMC. In order to make recommendations for improving the quality of KMC practice, the study also examines hypotheses that (1) Mothers' receptivity and responsiveness are critical to the implementation and practice of KMC and (2) Mothers receptivity and responsiveness are affected by (a) education and information, (b) nature and levels of support, and (c) general hospital conditions. In-depth interviews were conducted with thirty mothers in the East London Complex. Twenty participants were at CMH and ten at FH. One participant at each hospital was practising intermittent KMC. The findings of this qualitative study demonstrate clear consensus for the questions posed. The findings confirmed that KMC was positively received by mothers in a public hospital setting in South Africa but in order for the practice of KMC to be successful, attention should be paid to the following: (a) information received early and effectively, (b) KMC support in hospital and at home after discharge (c) improvement of hospital conditions. Recommendations based on these findings are included to improve the practice of KMC in hospital and at home after discharge.